Me and My Emotions: Learning to Manage Feelings and Behave Well at School - Putri, Intan Alifiah; Indahyani, Riska Nur; Madani, Ely Roy; Qur'aniyah, Millatil; Sintia, Rina; Halizah, Siti Nor; Falaasifah, Imroatul; Mardiyah, Khayatul; Woko, Putri Ainnur; Lestari, Tri Puji (Edumedia Solution, 2026)
Bullying is often interpreted as part of aggressive behavior. This aggressivebehavior is also caused by elementary school children's difficulty in regulating their emotions. Elementary school education is a particular focus because it is the level of education that experiences the most cases of bullying and violence. The psychoeducation program “Me and My Emotions: Learning to Manage Feelings and Behave Well at School” was conducted as a community service with the aim of increasing students' knowledge of emotional regulation skills as a means of preventing bullying behavior among 6th grade students at SDN 1 Curahmalang. The results of this effort show that psychoeducation provides significant benefits for participants. Of the 36 students who were given post-test questions, the results show that psychoeducation had a positive impact on participants. From these results, it can be concluded that psychoeducation hasan impact on good emotion management. In addition, students also showed an increase in understanding about bullying and efforts to improve emotional regulation as a preventive measure against bullying, both from the perpetrators and victims.